2021
DOI: 10.1155/2021/2577113
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis of Contrast Enhanced Ultrasound in Judging Benign and Malignant Thyroid Tumors

Abstract: In recent years, the incidence of thyroid cancer (TC) patients has gradually increased, and it ranks first among all endocrine tumors. TC has no obvious characteristics at the initial stage of onset. Thyroid tumors (TT) have formed when they are discovered, and they are easy to see when they are diagnosed. The disease is confused, so it is necessary to rely on imaging methods for tumor diagnosis. Contrast-enhanced ultrasound (CEUS), as the most commonly used imaging method in current clinical testing, is simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Additionally, CEUS is utilized in the field of interventional ultrasonography, which includes assisting biopsy and FNA procedures and estimating therapeutic conditions after ablation (11,12). Despite not being recommended as part of the guidelines for diagnosing thyroid nodules, numerous studies have demonstrated that CEUS exhibits a sensitivity and specificity of discriminating malignant nodules from benign nodules that could reach 0.87 and 0.83, respectively (13,14). The consensus on the qualitative and quantitative analysis of CEUS recommends that malignant characteristics include later wash-in, heterogeneous hypoenhancement, earlier wash-out, and centripetal perfusion (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CEUS is utilized in the field of interventional ultrasonography, which includes assisting biopsy and FNA procedures and estimating therapeutic conditions after ablation (11,12). Despite not being recommended as part of the guidelines for diagnosing thyroid nodules, numerous studies have demonstrated that CEUS exhibits a sensitivity and specificity of discriminating malignant nodules from benign nodules that could reach 0.87 and 0.83, respectively (13,14). The consensus on the qualitative and quantitative analysis of CEUS recommends that malignant characteristics include later wash-in, heterogeneous hypoenhancement, earlier wash-out, and centripetal perfusion (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compared with benign thyroid nodules, the degree of differentiation of newly formed vascular endothelial cells in malignant nodules is lower, the connections between cells are not as tight, and the terminals of the blood vessels are open. Therefore, CEUS can be used to differentiate between benign and malignant thyroid nodules according to their various pathological features (23)(24)(25). However, some studies pointed out that partial volume effect is enhanced due to the occurrence of small nodules in CEUS diagnosis of thyroid nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS) is a safe, convenient and cost-effective imaging modality, and approved for thyroid imaging [ 10 12 ]. Clinical evidence has confirmed that CEUS detects viable tissue by visualizing microvascular perfusion [ 13 ].…”
Section: Introductionmentioning
confidence: 99%